Development Of Wedding Planner Module Siapsiapnikah.com Using Extreme Programming Method - Eva Novianti; Yuli Adam Prasetyo; Taufik Nur Adi (eProceedings of Engineering, 2015)
Abstract— A plan usually made as a note and list on paper. Planning something as a small project or bigger need requirements to be noticed in the beginning. A project plan for wedding in Indonesia emerged as a special occasion to be prepared and theoretical important before marriage. Problem occurs at most is communication and product quality which handled by wedding organizer to bride and groom. Wedding organizer who want to handle a traditional wedding or international wedding need a complete information and requirement for the project and maintain the pre-wed schedule. Therefore, this research problem is how to develop a project management in application e-commerce for wedding organizer. This research will provide management based on time and quality on wedding planner within advertisement as revenue stream to the website and messaging as communication tool. The development of siapsiapnikah.com will use extreme programming method and implement project management plan to arrange the wedding. The development of siapsiapnikah.com will use CodeIgniter as a framework which is easier to continue on the next development. The final result of this research is e-commerce project management for wedding planner to help bride and groom to easily maintain their schedule with wedding organizer on their pre-wedding. Moreover, wedding organizer can share information using comment or messaging with bride and groom to maintain their activities and communications. Keywords— e-commerce, extreme programming, project management, wedding planner